ECONOMIC EFFICIENCY AND TECHNICAL JUSTIFICATION OF STRENGTHENING REINFORCED CONCRETE STRUCTURES WITH COMPOSITE MATERIALS IN COMPARISON WITH NEW CONSTRUCTION - Valovoi, Olexander; Valovoi, Maksym; Pastukhov, Stanislav; Malashenko, Victor (Current Problems of Sustainable Development, 2026)
The article examines the feasibility of restoring reinforced concrete structures instead of demolishing them. Since the damage to Ukraine’s infrastructure exceeds 176 billion US dollars and total reconstruction needs surpass 524 billion, the search for effective rebuilding methods is becoming critical. The aim of the work is the technical and economic justification of methods of cross-section enlargement of damaged elements with innovative composite materials in comparison with new construction. The methodology relies on a non-linear deformation model and the finite element method, which makes it possible to analyse the stress-strain state of structures strengthened directly under the action of operational loading. The actual coefficients of the working conditions of the additional reinforcement, which formally describe the ratio of the actual relative strains to their limiting values, are taken into account. The technical part of the study shows the high efficiency of combined strengthening: the application of carbon-fibre composite tapes in the tensile zone of bent reinforced concrete elements together with the build-up of the compressed zone by an additional layer of concrete (overlay) made of steel-fibre-reinforced concrete, reactive-powder concrete or with basalt-fibre-reinforced polymer reinforcement (BFRP). The economic part of the study uses mathematical financial modelling that compares the costs of revitalisation (modernisation of the building core, spatial adaptation and modernisation of engineering systems) with the costs of complete demolition and new construction (demolition, debris removal, new construction). The environmental benefit (avoided CO₂ emissions and reduced construction waste) is also taken into account. The key indicator of comparison is the Savings Ratio, which accumulates both direct financial savings and monetised environmental advantages. Using the example of the revitalisation of the Radex Park Marywilska industrial complex, the considerable macroeconomic prospects of such solutions are proven. It is established that adaptive reuse provides the necessary level of structural reliability and makes it possible to reach a Savings Ratio of 1.93, preserving almost 57 % of capital expenditures and reducing carbon emissions in comparison with the construction of new buildings. The proposed approach is consistent with the European principles of the circular economy and is recognised as one of the most rational and cost-effective approaches to Ukraine’s post-war reconstruction.